Halal Business Activity Efforts by Applying the Principle of Muamalah in Islamic Economic Transactions - Isman Ahadi Lebu Raya; Ahmad Fauzi Tidjani (Values: Jurnal Kajian Islam Multidisiplin, 2024)
This research discusses halal business activity efforts that apply muamalah to Islamic transactions. The purpose of this research is to find out the definition, principles and activities of halal business with Islamic economics to find suitable results of efforts in implementing halal business activities in accordance with the Al-Qur'an and Hadith. In Islamic economic activities, it plays a quite important role in buying and selling in the lives of Muslims, as is the main requirement as one of the essence of Islamic teachings. The economy carried out by a Muslim is part of worshiping Allah SWT, which contains monotheism. Apart from that, Islamic economics aims to achieve balanced happiness between this world and the hereafter. Therefore, there are various efforts in implementing halal business activities by abandoning the various prohibitions that Allah SWT has set, establishing and adhering to the principles stated in the Al-Qur'an and Hadith, so that they can achieve their goals, because the concept of muamalah in Islam emphasizes Economic transactions must be based on moral values related to life between humans and Allah SWT.